2009
DOI: 10.1111/j.1469-0691.2008.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila pneumoniae diagnostics: importance of methodology in relation to timing of sampling

Abstract: The diagnostic impact of PCR-based detection was compared to single-serum IgM antibody measurement and IgG antibody seroconversion during an outbreak of Chlamydophila pneumoniae in a military community. Nasopharyngeal swabs for PCR-based detection, and serum, were obtained from 127 conscripts during the outbreak. Serum, drawn many months before the outbreak, provided the baseline antibody status. C. pneumoniae IgM and IgG antibodies were assayed using microimmunofluorescence (MIF), enzyme immunoassay (EIA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
(46 reference statements)
0
23
0
3
Order By: Relevance
“…In investigations without controls, C. pneumoniae DNA was found in 5% to 26% of patients diagnosed with acute respiratory infections such as CAP or bronchitis [20,39,41,42]. Miyashita and colleagues found that 8% of patients with acute respiratory disease had DNA in their respiratory samples, compared with 3% of asymptomatic controls [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In investigations without controls, C. pneumoniae DNA was found in 5% to 26% of patients diagnosed with acute respiratory infections such as CAP or bronchitis [20,39,41,42]. Miyashita and colleagues found that 8% of patients with acute respiratory disease had DNA in their respiratory samples, compared with 3% of asymptomatic controls [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigations are necessary to elucidate the etiology of C. pneumoniae in CAP in Jordanian nationals. On the basis of previous findings [41,46,47], reliable, and sensitive diagnostic tests such as validated real-time PCR alone or combined with specific IgM-detecting method should be used to define cases of acute respiratory C. pneumoniae infection. Importantly, C. pneumoniae can be found in association with other CAP etiologic agents such as Streptococcus pneumoniae and Mycoplasma pneumoniae [13].…”
Section: Discussionmentioning
confidence: 99%
“…15,22,23 The serum antibodies to C. pneumoniae reach a diagnostic level 6 to 8 weeks after the exposure and infection of C. pneumonia, and the seropositivity remains for life. [24][25][26] The value (optical density) of seropositivity for C. pneumoniae is greater than 0.9 as reported in a paper written in Japanese using this ELISA kit. 27 Laboratory personnel were masked to clinical and demographic information on the patients.…”
Section: Serologic Testsmentioning
confidence: 95%
“…Für die Detektion atypischer Pathogene sind die Tests validiert und die Ergebnisse so schnell verfügbar, dass sie auch therapeutisch relevant sind [24,25,26].…”
Section: Streptococcus Pneumoniae Ist Auch Bei Pleuraerguss Möglichunclassified
“…Wenn die ätio logische Diagnostik von atypischen Erregern erforderlich ist, sollten serologische Tests nicht als der einzige Routinetest durchgeführt werden. In diesem Fall ist die Kombination aus der Bestimmung von IgM-Antikörpern und einer PCR der Ansatz mit der höchsten Sensitivität [21,25,26].…”
Section: Serologische Tests In Der Cap-diagnostikunclassified